Scientific Literacy Research in Physics Education: A Comprehensive Bibliometric Analysis and Future Research Directions - Indri Maya Ariana; Khofifatur Risma Faradillah; Muhammad Ghiyats Naufal; Adrian Bagas Damarsha; Titin Sunarti; Hanandita Veda Saphira (Berkala Ilmiah Pendidikan Fisika, 2026)
Science literacy is an essential 21st-century competency that encompasses not only an understanding of scientific concepts but also critical thinking skills, environmental awareness, and the ability to address global issues. Although attention to science literacy is increasing, research in this field remains fragmented and lacks comprehensive mapping. This study offers novelty through the application of bibliometric analysis to map trends, contributions, directions, and opportunities for science literacy research in the context of education. Data were collected from the Scopus database for the period 2014–2024 using the keywords “scientific literacy” and “education,” then analyzed with RStudio software and bibliometric visualization. The results show a significant upward trend in publications since 2017, with Indonesia making the dominant contribution. Future research directions are moving towards integrating scientific literacy with digital technology, understanding the nature of science and its relevance to global issues such as socio-scientific issues and global warming, and developing critical thinking skills. Thus, scientific literacy is positioned not only as a cognitive domain but also as a strategic tool for students to face the dynamics and challenges of the modern world. The results of this study have important implications for the development of a more contextual, innovative, and digitally integrated curriculum and for guiding future research that links science literacy with cross-cutting issues such as environment, technology, society, culture, and local wisdom to enrich perspectives and research directions.